Thermodynamic analysis and performance optimization of transcritical power cycles using CO2-based binary zeotropic mixtures as working fluids for geothermal power plants - Wu, Chuang; Wang, Shun-sen; Jiang, Xihang; Li, Jun (Applied thermal engineering, 2017)
•TPCs with CO2-based binary zeotropic mixtures are investigated for low-temperature geothermal power plants.•Parametric optimization is performed by the pattern search algorithm (PSA).•Exergy, exergy and economic analyses are conducted. Transcritical power cycles (TPCs) using CO2-based binary zeotropic mixtures for the conversion of low-grade geothermal water at 100–150°C into power are presented and analyzed when cooling water temperature (Tcw) is 10–30°C in this paper. 6 refrigerants are selected as the additives into CO2 according to 2 criteria. Performances of TPCs with 6 selected CO2-based mixtures are optimized by pattern search algorithm (PSA). Thermodynamic and economic analyses are conducted. The results reveal that R161/CO2 is the best fluid for a TPC in terms of both thermal performance and economic performance while R290/CO2 might be an unsuitable working fluid in TPC due to its lower thermal performance. When Tcw=10–20°C, a TPC using R161/CO2 at XR161=0.7 can increase net power output by 14.43–50.46% and decrease cost per net power by 27.96–48.72% compared with a TPC using CO2. The selected CO2-based mixtures can reduce CPP of a TPC compared with CO2 although more heat transfer area is required. Meanwhile, the CO2-based mixtures can decrease the high operating pressure, and enlarge the condensing temperature range compared with CO2. In addition, the CO2-based mixtures except R161/CO2 and R152a/CO2 are not recommended for a TPC when Tcw is low.